Community optometrist referral of those aged 65 and over for raised IOP post-NICE: AOP guidance versus joint college guidance—an epidemiological model using BEAP. Issue 11 (10th February 2011) - Vernon, S A; Hillman, J G; MacNab, H K; Bacon, P; van der Hoek, J; Vernon, O K; Bhargarva, A
Abstract : Background/aims: To identify the percentage of those aged 65 and over who might be referred by community optometrists as ocular hypertensive suspects in the post-NICE era when differing guidance is followed by community optometrists. Method: The authors constructed an epidemiologically based model utilising Bridlington Eye Assessment Project (BEAP) data. Ocular hypertensive suspects' data were subjected to two algorithms (Association of Optometrists (AOP) and Joint College) to determine referral of suspects if community optometrists followed either algorithm. Results: 85 of 1643 people (5.2%) tested by BEAP, with normal acuity and visual fields, recorded Goldmann IOPs of >21 mm Hg in either or both eyes. Without pachymetric information, all 85 would be referred under the AOP algorithm, decreasing to 31 (1.9%) under the joint College algorithm (63% reduction). If central corneal thickness readings influenced referral, 39 (2.4%) would be referred under the AOP algorithm and 13 (0.8%) under the joint College algorithm. Conclusion: If community optometrists use Goldmann tonometry and pachymetry, following the joint College guidelines, referrals of OHT suspects could be reduced to a fifth of those under the original AOP guidance. Community optometrists should be encouraged to use GAT and pachymetry in order to refine referrals when another examination is normal. Potential savings to the NHS are considerable.